Enhancing women’s economic empowerment in rural Nigeria through advocacy trainings - Kosec, Katrina; Kyle, Jordan; Mo, Cecilia H. (International Food Policy Research Institute, 2024)
This policy brief shares quantitative results from a project examining the effectiveness of advocacy and leadership training for women, along with allyship training for men (their husbands), in improving women’s economic outcomes. We share insights from a randomized controlled trial (RCT) conducted across three states of southwestern Nigeria (Oyo, Ogun, and Osun) involving over 5,800 women participants from 450 communities. We causally test whether training women alone, as well as whether training them in tandem (though in separate sessions) with their husbands, can increase women’s access to and investments in livelihood opportunities. While the trainings were designed to train women in the skills needed for engaging in the local policy process in rural communities in Nigeria and to train their husbands on the benefits of women’s participation in community affairs as well as in how to practically support their wives’ participation, we posit that increased efficacy combined with advocacy skills and husbands’ support could additionally have profound economic spillovers. Indeed, we show causal improvements in these outcomes when women are trained and present some emerging policy lessons.